BEYOND PHILANTHROPY: DECOUPLING AND GREENWASHING DALAM PELAPORAN CSR SERTA PERSPEKTIF INSTITUSIONALISME KOMPARATIF ANTARA INDONESIA DAN MALAYSIA - Noufal Muksalmina; Riski Maulana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to evaluate the quality, transparency, and integrity of Corporate Social Responsibility (CSR) disclosure practices in the conventional and Islamic banking sectors in Indonesia and Malaysia. Using the lens of Institutional Theory, this study examines how differences in regulatory pressure, namely the mandatory model through POJK 51/2017 in Indonesia and the Value-based Intermediation (VBI) framework in Malaysia affect corporate reporting behavior. Through a descriptive quantitative approach and comparative content analysis of annual reports and sustainability reports for the 2019– 2020 period, the level of disclosure was measured using the Global Reporting Initiative (GRI) and Islamic Social Reporting (ISR) indices. The findings reveal significant differences in reporting priorities and depth triggered by each country's regulatory structure. Banking in Malaysia shows a higher level of maturity in environmental and governance (ESG) aspects as a result of the systematic implementation of VBI, although this market structure also creates loopholes for greenwashing through sophisticated green narratives. In contrast, Indonesian banks, particularly Islamic banks, show excellence in the dimensions of philanthropy and community engagement based on Maqasid Syariah. However, this study also finds indications of decoupling, where legal formalism in Indonesia tends to encourage superficial administrative compliance, so that CSR disclosure often serves only as a symbolic legitimization tool rather than a substantive commitment. Overall, these results confirm that regulatory pressure is crucial in determining whether CSR disclosure will be honest transparency or merely a corporate image strategy.